Atmospheric plasma treatment: an alternative of HF etching in lithium disilicate glass-ceramic cementation - Wu, Xiaoqian; Liu, Kun; Luo, Rui; Xu, Jianhao; Chen, Mingsheng (Frontiers in Bioengineering and Biotechnology, 2023)
Objectives: This study aimed to investigate whether the atmospheric pressure plasma jet (APPJ) could modify the surface of lithium disilicate glass ceramics (LDC) instead of hydrofluoric acid (HF) in LDC resin cementation.Methods: 162 232 LDC blocks were randomly divided into 7 groups: Group 1 (16 specimens) was the blank control group (without HF or APPJ treatment); Group 2 (36 specimens) was etched by HF; Groups 3-7 (36 specimens each) were treated with APPJ, and the relative air humidity (RAH) of the discharge was 22.8%, 43.6%, 59.4%, 75.2%, and 94.0%, respectively. 3 LDC blocks in each group were characterized via X-ray photoemission spectroscopy (XPS) analyses, and other 3 blocks via contact angle measurements, and other 10 blocks via surface roughness measurements. The residual LDC blocks in groups 2-7 were cemented to composite cylinders.Testing the cemented specimens' shear bond strength (SBS) before and after thermocycling (6,500 cycles of 5℃ and 55℃) revealed fracture patterns. Data were analyzed by ANOVA (post hoc: Bonferroni) (α = 0.05).Results: After APPJ treatment, the water contact angle values of APPJ treated blocks dropped from 31.37° to 5.66°, while that of HF etched ones dropped to 18.33°. The O/C ratio increased after HF etching or APPJ treatment according to the calculated results, except for the APPJ-treated samples at a RAH of 22.8%. The surface roughness of LDC blocks showed no statistic difference before and after APPJ treatment, but experienced significant difference after HF etching.2 compared to that of the blank control group. The O/Si and O/C ratios variedincreased after HF etching or APPJ treatment. No significant difference in SBS values could be found among groups 2-7 before or after artificial aging (P＞0.05). All specimens showed mixed failure patterns.The APPJ treatment method reported in this study is a promising novel strategy for surface modification of the LDC. With acceptable satisfactory bonding strength, it might be an alternative to HF in LDC-resin cementation.